“Peaceful and exemplary”. Notes for a review of the role of the armed left in the spanish transition - Galiana Cano, Vicent (Revista de Historia Social y de las Mentalidades, 2024)
The changes in the last decades around the study of the Spanish political transition has carried to the identification of social majority as the driving force in political change. Despite this, the Armed Left has been set aside in most of the investigations, narrations and chronicles of the period. This article hopes to revise in a critical way some of the hegemonic interpretations of the Spanish transition, as well as to provide some keys to make progress in the study of the Armed Left linked to national liberation as an involved agent in the transitional process.
Keywords: Spanish Transition; Social Movements; Political Violence; Armed Left